2021
DOI: 10.1136/bmj.n2031
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: Children born during the pandemic score lower on cognitive tests, study finds

Owen Dyer

Abstract: Children born during the pandemic score markedly lower on standard measures of verbal, motor, and overall cognitive ability, US researchers have found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…However, some literature states that SARS-CoV-2 infection in pregnant women in the second and third trimesters increases obstetric and neonatal risks and improves baby care in the NICU (Neonatal Intensive Care Unit) ( Badr et al, 2021) (Wei et al, 2021). This is in line with a retrospective cohort study of infants born to mothers with severe COVID-19 associated with NICU care and growth retardation (Hamidi et al, 2022) Toddlers born during the COVID-19 pandemic show a significant or low overall verbal, non-verbal, motor, and cognitive decline compared to toddlers born before the COVID-19 pandemic (Deoni et al, 2021) (Dyer, 2021). According to (Naidu et al, 2022) the cytokine storm induced during COVID-19 in Pregnancy can cause severe inflammatory damage to the fetus, and if not controlled, can later lead to disorders such as autism spectrum and brain development abnormalities in the neonate.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, some literature states that SARS-CoV-2 infection in pregnant women in the second and third trimesters increases obstetric and neonatal risks and improves baby care in the NICU (Neonatal Intensive Care Unit) ( Badr et al, 2021) (Wei et al, 2021). This is in line with a retrospective cohort study of infants born to mothers with severe COVID-19 associated with NICU care and growth retardation (Hamidi et al, 2022) Toddlers born during the COVID-19 pandemic show a significant or low overall verbal, non-verbal, motor, and cognitive decline compared to toddlers born before the COVID-19 pandemic (Deoni et al, 2021) (Dyer, 2021). According to (Naidu et al, 2022) the cytokine storm induced during COVID-19 in Pregnancy can cause severe inflammatory damage to the fetus, and if not controlled, can later lead to disorders such as autism spectrum and brain development abnormalities in the neonate.…”
Section: Introductionsupporting
confidence: 75%
“…The study states that children born in 2019 before the COVID-19 pandemic did not experience a decrease in developmental scores, compared to children born in 2020 at the start of the COVID-19 pandemic and in 2021 measurements of gross motor, fine motor, visual and language development were carried out. children have developmental deficiencies (Dyer, 2021). Likewise toddlers born to mothers confirmed to have COVID-19 at the age of experiencing developmental disorders in communication, gross motor, fine motor, problemsolving, and social (Shah et al, 2023) (Cheng et al, 2021).…”
Section: Characteristics Of Toddlersmentioning
confidence: 99%
“…Children born during the COVID-19 pandemic have lower scores on cognitive tests. 38 This problem was even worse for the developing children from families with low socioeconomic status. 39 Therefore, it may be recommended to conduct social and communicative screening in young children after the pandemic and to focus more on the development of language and communication skills.…”
Section: Child Developmental Effectsmentioning
confidence: 99%
“…In a study conducted in the United States (US), it was found that children born during the pandemic scored significantly lower in verbal, motor, and general cognitive ability measurements. A cohort study conducted since 2011 indicated that those born after the pandemic began had an average IQ score 22 points lower than previous cohorts, with an average of 78 points 8 .…”
Section: Introductionmentioning
confidence: 99%